A systematic investigation of the association between HPV and the clinicopathological parameters and prognosis of oral and oropharyngeal squamous cell carcinomas. (4th April 2017) - Wang, Fengze; Zhang, Hui; Xue, Yang; Wen, Jiao; Zhou, Jun; Yang, Xinjie; Wei, Jianhua
Abstract: Human papillomavirus (HPV), the causal factor of cervical cancers, was closely linked to the etiology and prognosis of oropharyngeal squamous cell carcinoma (OPSCC), but its role in oral squamous cell carcinoma (OSCC) was unclear. In addition, few researches based on Chinese population were documented. Hence, we sought to investigate the relationship of HPV marker P16 protein to the clinicopathological parameters and survival of OPSCC and OSCC patients systematically to assess the influence of ethnic, regional difference on HPV susceptibility. Specimens from 93 OPSCC patients and 95 OSCC patients were recut, and P16 immunohistochemistry (IHC) was performed. Moreover, survival analysis was conducted to confirm the independent factors that influenced the prognosis. The P16 results were positive in 25.8% and 9.5% of patients with OPSCC and OSCC, respectively. The overall survival (OS) of HPV‐positive OPSCC patients was significantly longer than that of HPV‐negative OPSCC patients ( P = 0.004). Conversely, statistical significance was not observed regarding the OS of OSCC patients ( P = 0.343). Cox regression analysis indicated that T stage and P16 status were independent factors that affected the prognosis of OPSCC patients, and the smoking index influenced the prognosis of OSCC patients. Among OPSCC patients who received radiochemotherapy (RCT), HPV‐positive patients had a better survival rate than their HPV‐negative counterparts ( P = 0.015). Conversely, no significant difference was observed between HPV‐positive and HPV‐negative OSCC patients who received RCT ( P = 0.237). P16 is a credible surrogate by which to define HPV status. HPV expression had a favorable effect on OPSCC patients as opposed to their OSCC counterparts in this single center population‐based study. Abstract : The research regarding to the relationship between HPV and clinicopathological parameters and paprognosis of oral and oropharyngeal squamous cell carcinomas is emerging as a hotspot in the world. Taking account of the difference between The East and The West, we conduct this systematic retrospective investigation including consultation of medical records, collection of specimen, statistical analysis and postoperative follow‐up.